2020
DOI: 10.1091/mbc.e19-09-0499
|View full text |Cite
|
Sign up to set email alerts
|

Novel fibrillar structure in the inversin compartment of primary cilia revealed by 3D single-molecule superresolution microscopy

Abstract: Using three-dimensional single-molecule superresolution imaging and systematic analysis of knockout cell lines, we have determined the molecular structure and composition of the inversin compartment in primary cilia. INVS establishes fibrillar structures that recruit ANKS6-NEK8 complexes to sequester NPHP3 in this unique periaxonemal compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 64 publications
4
35
0
Order By: Relevance
“…The axonemal localization of ENKD1 depends on its ability to interact with microtubules, further supporting its functions as a ciliary MAP. Notably, the length of the ENKD1-positive axoneme relative to the cilium length substantially varied from cilium to cilium, which was previously reported for components of the Inversin compartment of primary cilium (Bennett et al, 2020). Because ENKD1 did not localize with inversin, this result suggests that ENKD1 association with the ciliary axoneme might require specific tubulin modifications or ciliary binding partners.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The axonemal localization of ENKD1 depends on its ability to interact with microtubules, further supporting its functions as a ciliary MAP. Notably, the length of the ENKD1-positive axoneme relative to the cilium length substantially varied from cilium to cilium, which was previously reported for components of the Inversin compartment of primary cilium (Bennett et al, 2020). Because ENKD1 did not localize with inversin, this result suggests that ENKD1 association with the ciliary axoneme might require specific tubulin modifications or ciliary binding partners.…”
Section: Discussionsupporting
confidence: 59%
“…1F, 1G, 1H). To further define the ciliary sub-compartmentalization of ENKD1, we determined its localization relative to the proximal axoneme modified by polyglutamylation as well as the inversin compartment, which was shown to vary in length from cilium to cilium (Bennett et al, 2020;Sang et al, 2011). mNG-ENKD1 did not co-localize with polyglutamylated tubulin and mScarlet-INVS, suggesting that ciliary proteins or modifications other than polyglutamylation and inversin might regulate its ciliary incorporation (Fig.…”
Section: Enkd1 Localizes To the Centrosomes And Primary Ciliamentioning
confidence: 99%
“…We previously showed that Arl13b and Inpp5e localized to collecting duct cilia and localization was reduced in both Hoxb7-Cre; Tulp3 f/f and Ksp-Cre; Tulp3 f/f collecting duct cilia by P5 (Hwang et al, 2019). Nphp3 localizes to the proximal inversin zone in cilia (Bennett et al, 2020) but localization in kidney collecting ducts is unknown. Lkb1 has been reported to localize to kidney collecting duct cilia (Viau et al, 2018).…”
Section: Tulp3 Is Required For Ciliary Localization Of Lipidated Proteins In Murine Kidneysmentioning
confidence: 99%
“…The effectiveness for complete depletion of Inpp5e in cilia in Tulp3 ko might be related to direct binding between Arl13b and Inpp5e and requirement of such binding for effective ciliary retention of Inpp5e (Humbert et al, 2012;Qiu et al, 2021). Nphp3 is concentrated in the proximal ciliary inversin compartment by binding to Nek8 and Anks6 that are required downstream of Inversin for Nphp3 localization (Bennett et al, 2020). Such binding might promote some retention of Nphp3 even in the absence of Tulp3.…”
Section: Tulp3 Enriches Arl13b-dependent Lipidated Proteins In Ciliamentioning
confidence: 99%
“…Two facts support the latter model; first, most of the spontaneous Ca 2+ activity and GABA-induced activity originated in the distal parts of the cilium (see Fig. 6), and second the inversin compartment has been hypothesized to work by sequestering ciliary proteins and releasing them under appropriate stimulation 32 . To test this, we analyzed the GABA-B1 receptor distribution after a short (10 min) stimulation with GABA or the GABA-B receptor agonist baclofen.…”
Section: Resultsmentioning
confidence: 82%